Performing the US Latina and Latino borderlands - Aldama, Arturo J., 1964-; Sandoval, Chela, 1956-; García, Peter J. (Indiana University Press, 2012)
In this interdisciplinary volume, contributors analyze the expression of Latina/o cultural identity through performance. With music theater, dance, visual arts, body art, spoken word, performance activism, fashion, and street theater as points of entry, contributors discuss cultural practices and the fashoning of identity in Latino/a communities throughout the US. Examining the areas of crossover between Latin and American cultures gives new meaning to the notion of "borderlands." This volume features senior scholars and up-and-coming academics from cultural, visual, and performance studies, folklore, and ethnomusicology